A study on the socio economic realities of Bangladesh based dancers: understanding their financial struggles and industry issues that set dance as a marginalized profession in Bangladesh - Mela, Lamia Saiyara (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2019.